(3QSGdI aj eYQaI hVY NWhW aVd GdOGFQ Ydi GdHSGFW hGdbGFeGJ hGdeGFdGJs - (3GHf GdeLOj, CHh GdYHGS, TgGH GdOjf, CMeO Hf QLH Hf WfHZG, (B850 (3g`s
(3ChdgG (B:s
(3GdMeO ddg agPg QSGdI GdI aj eYQaI hVY NWhW aVd GdOGFQ Ydi GdHSGFW hGdbGFeGJ hGdeGFdGJ dNUJgG ef cJGHj GdeSei HEQTGO GdMGFQ Edi eYQaI hVY NWhW aVd GdOGFQ eY RjGOGJs
(3BNQgG (B:s
(3aEf LgdJ fbWI GdbWH aCNQL NWjf ef NWhW aVd GdOGFQ Ydi GSJbGeI MJi jdJbjG aKe ehVY GdbWH aEf JhGRJ NWhW aVd GdOGFQ adG hLhO ddbWH Ydi Pdc GdSWM Jes
(3Vef eLehY NRGFfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\125s
(3cTa GdXfhf (B1\64s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3Gdadc hGdJfLje hGdejbGJs